PENGARUH PENGGUNAAN BUBUK JAHE MERAH (Zingiber officinale var. Rubrum) TERHADAP SIFAT ORGANOLEPTIK BAKSO DAGING KAMBING - Armansyah,, Afikra; Ratulangi, Friets S.; Rembet, Godlief D.G. (Universitas Sam Ratulangi, 2018)
THE UTILIZATION OF RED GINGER POWDER (Zingiber officinale var. Rubrum) ON ORGANOLEPTIC CHARACTERISTIC OF MUTTON MEATBALLS. This study was conducted to evaluate the utilization of red ginger powder on the organoleptic characteristic of mutton meatballs. The materials used were fresh mutton meat on the hamstrings, tapioca flour, salt, flavoring, garlic, pepper, red ginger powder, ice cubes and processing equipment tools. The experimental design used in this study was a Completely Randomized Design of five treatments with 30 replications. The treatment was 300 g of meat and 0 g red ginger powder (R0), 300 g of meat and 1.5 g red ginger powder (R1), 300 g of meat and 3.0 g red ginger powder (R2), 300 g of meat and 4.5 g red ginger powder (R3), and 300 g of meat and 6 g red ginger powder (R4). Organoleptic testing performed was using the hedonic quality test. The variables measured consisted of color, flavor, taste and elasticity of meatballs. Determination of the average difference among treatments was done by Tukey (HSD) test. The results showed that the treatments affected significantly on flavor and taste. However, treatments did not affect significantly on color and elasticity of meatballs. The use of 3g red ginger powder could provide acceptance levels on organoleptic characteristic of mutton meatballs.Â Keywords: Mutton meat, red ginger, Meatballs